2021
DOI: 10.3390/ijerph18084253
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Nursing Needs of Parents with Pediatric Cancer Patients in Different Treatment Phases: A Cross-Sectional Study

Abstract: The survival rate of pediatric cancer has increased to 80%, but long-term treatment is required. During treatment, parents experience uncertainty, which affects parents’ quality of life and, even worse, their children’s health; however, the variation of that uncertainty remains under-studied. Thus, it is crucial to understand parents’ nursing needs in each distinct treatment phase to develop relevant educational content. This study investigated the uncertainty level and nursing needs of parents according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In addition to the place of residence, children's stool traits were also the factors affecting the parents' nursing needs ( p < 0.001), that is, the stool traits were assessed according to the Bristol stool scale, and the harder the stool trait, the higher the parental needs score. This is consistent with the findings of the same type of research ( 39 , 40 ). A previous study showed that large and hard stool was the most frequent symptom among children with functional constipation, hard stool consistency was found in about 93.7% of cases ( 41 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the place of residence, children's stool traits were also the factors affecting the parents' nursing needs ( p < 0.001), that is, the stool traits were assessed according to the Bristol stool scale, and the harder the stool trait, the higher the parental needs score. This is consistent with the findings of the same type of research ( 39 , 40 ). A previous study showed that large and hard stool was the most frequent symptom among children with functional constipation, hard stool consistency was found in about 93.7% of cases ( 41 ).…”
Section: Discussionsupporting
confidence: 93%
“…Both FoP scores and proportions of dysfunctional levels of FoP in our cohort were higher than those reported in parents of childhood cancer survivors 6 ; the difference may be attributed to different measurement time points. Previous studies have also demonstrated higher levels of PTSS and uncertainty in parents of children undergoing cancer treatment than in those who had completed treatment 31,32 . Notably, the FoP scores and proportions of dysfunctional levels FoP reported in our sample were significantly higher than those of adult cancer patients and their partners 8 .…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies have also demonstrated higher levels of PTSS and uncertainty in parents of children undergoing cancer treatment than in those who had completed treatment. 31,32 Notably, the FoP scores and proportions of dysfunctional levels FoP reported in our sample were significantly higher than those of adult cancer patients and their partners. 8 Unlike the partners of adult patients, parents are fully responsible for the care of their child; they therefore experience extreme stress and uncertainty, which may place them at a high risk of elevated FoP.…”
Section: Discussionmentioning
confidence: 57%
“…Parents’ knowledge about appropriate home caregiving influences their caregiving practices for the child [ 10 ]. However, parents may have inadequate caregiving knowledge including infection prevention, managing side effects of treatment, and providing emotional support for their child [ 11 ]. Therefore, caregivers’ knowledge in these areas needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%